Gender, informality and urban livelihoods: examining the livelihood strategies adopted by Black female street vendors in Makhanda, Eastern Cape - Khoele, Lineo (Rhodes University, Faculty of Humanities, Department of Sociology)
This study sought to examine livelihood strategies adopted by black female street vendors in Makhanda, Eastern Cape. The street vending activities that were undertaken by the research participants included selling: cooked foods, fresh fruit and vegetables, eggs, and beauty products. This study used the Sustainable Livelihood Approach (SLA) to examine the livelihood strategies of black female street vendors in Makhanda. The SL approach was chosen as an ideal framework for a study of this nature as it holistically and traditionally focuses on vulnerable population groups around the world. More importantly, the SLA gives agency to these vulnerable groups, as it prioritizes their innovative techniques in mobilizing diverse assets at their disposal in order to survive. The study is, therefore, ideal as it also gives agency to selected black female street vendors by examining how they utilized diverse assets at their disposal to sustain their livelihoods. This study seeks to contribute to the ongoing debate on urban livelihoods and the informal economy in South Africa, focusing particularly on the different methods or strategies employed by black female street vendors to enhance the sustainability of street vending as a livelihood. Due to the nature of this study, which seeks to capture the lived experiences of the selected black female street vendors in Makhanda, qualitative research methodologies were used to collect and analyse data. This study proved street vending to be a survival strategy that is used by black unskilled women in pursuit of livelihoods. It argues that, faced with the socio-economic realities associated with high unemployment, street vending can be used by many to best support their households. When it comes to livelihood strategies, this study found that, livelihood diversification is the most common livelihood strategy adopted by street vendors in Makhanda, with the only difference being the type of diversification adopted. Two forms of livelihood diversification strategies were identified in this study, and these included: product diversification and income diversification. The conclusion drawn from the findings argues that the selected street vendors in Makhanda strategically used different assets accessible to them to enhance and sustain their livelihoods. The study found that despite the different structural challenges faced by street vendors in Makhanda, the selected black female street vendors are able to meet their livelihood outcomes and support their families through engaging in street vending.
Keywords: Livelihood; Street vendors -- South Africa -- Eastern Cape; Women, Black Social conditions; Informal sector (Economics) Social aspects -- South Africa -- Eastern Cape